How Ornamental Fish Get Their Color - Frank A. Chapman; Richard D. Miles (EDIS)
Color in fish is mostly genetically determined, but they are unable to produce red, orange, yellow, green, and some blue colors themselves. They get these colors from their food. Fish raised in aquariums or recirculating water systems without pigment supplementation in their diet will fade and lose their vibrant hues. Even in ponds, dietary pigment supplementation can make fishes brighter and more variably colored, just like their wild counterparts. This 6-page fact sheet written by F. A. Chapman and R. D. Miles and published by the UF/IFAS School of Forest Resources and Conservation, Program in Fisheries and Aquatic Sciences, addresses how ornamental fish get their colors and provides a list of ingredient sources for diets that can be used to enhance and intensify fish colors. http://edis.ifas.ufl.edu/fa192